Monitoring summertime indoor overheating and pollutant risks and natural ventilation patterns of seniors in public housing. Issue 5 (June 2023) - Tsoulou, Ioanna; He, Ruikang; Senick, Jennifer; Mainelis, Gediminas; Andrews, Clinton J
Indoor heat and air pollution pose concurrent threats to human health and wellbeing, and their effects are more pronounced for vulnerable individuals. This study investigates exposures to summertime indoor overheating and airborne particulate matter (PM2.5 ) experienced by low-income seniors and explores the potential of natural ventilation on maintaining good indoor thermal conditions and air quality (IAQ). Environmental and behavioural monitoring and a series of interviews were conducted during summer 2017 in 24 senior apartments on three public housing sites in NJ, USA (1930s' low-rise, 1960s' high-rise and LEED-certified 2010s' mid-rise). All sites had high exposures to overheating and PM2.5 concentrations during heat waves and on regular summer days, but with substantial between-site and between-apartment variability. Overheating was higher in the 30s' low-rise site, while pollutant levels were higher in the 60s' high-rise. Mixed linear models indicated a thermal and air quality trade-off with window opening (WO), especially in some 'smoking' units from the older sites, but also improved both thermal and PM2.5 concentration conditions in 20% of the apartments. Findings suggest that with warmer future summers, greater focus is needed on the interdependencies among (1) thermal and IAQ outcomes and (2) technological and behavioural dimensions of efforts to improve comfort for vulnerable occupants.